(untitled) (Bangladesh Journal of Medical Science, 2025)
Reflective writing (RW) is an analytical reflective practice method implemented in academic settings to encourage personal and professional growth. This qualitative study aimed to explore the perception of medical students on reflection, the process of RW and its associated challenges. A total of 30 students were invited to participate in focus group discussions (FGD). Five FGDs were conducted while facilitated by a moderator based on an unvarying set of 9 questions determined by researchers preceding data collection. Recordings of the FGD were transcribed and analysed thematically. A total of 39 codes were identified and classified into 11 themes. The themes are time spent, language barrier, impact of reflection, feedback, purpose of reflection, themes, frequency of assignments, word count, and suggested improvements. Results have shown assessment and grading reflective assignments should be re-evaluated or made obsolete to achieve its purpose as reflection is highly subjective. Ensuring consistent feedback from supervisors allow students to feel acknowledged and promote genuine reflections. Students also prefer verbal or discussion-based reflections compared to written form. The perception of students was found to be varying. While some students were doubtful of RW, the general concession was that it is a useful tool in reflective learning. It is important for institutions to review the enhancements suggested by students to further improve reflective practice in medical education. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 87-96